Optimization of Document Management to Improve Services for Prospective Hajj Pilgrims at the Ministry of Religious Affairs Office In Bukittinggi City - Puspita Sari, Romida; Nurani, Khadijah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This research is motivated by the existence of problems in the mechanism of optimizing the management of Hajj registration documents which are sometimes hampered by the network, and the lack of knowledge of prospective pilgrims in the Hajj registration process so that errors in the Pilgrim's data often occur. This study aims to study how to optimize the document management process as a service provided to prospective pilgrims and the relationship between the document management process and the services provided to prospective pilgrims. This study uses a qualitative research approach. This study uses a descriptive qualitative approach. The data used consists of primary and secondary data. Primary data comes from employees of the Hajj and Umrah Organizers of the Ministry of Religious Affairs of Bukittinggi City and is obtained through observation, interviews, and documentation. The results of the research obtained by the author indicate that the Ministry of Religious Affairs of Bukittinggi City has managed Hajj documents effectively and efficiently according to the optimization theory by Poerwadarminta. Document management is carried out well using an IT-based system in its management, and continues to make optimization efforts in managing Hajj documents so that Hajj document management services run optimally. And the management of Hajj documents is included in the services for Hajj pilgrims because in its implementation, services are provided in the form of verbal, written and deeds which are applied very well by Hajj officers.